Competencies Assessment in Higher Education: Experiences in the Mexican Context - Frida Díaz Barriga Arceo (Universidad Autónoma de Madrid, 2019)
A balance of the rapprochement of the competency approach in Mexican higher education during the last decades in relation to different tendencies and processes of appropriation is offered. Based on the sociocultural current and the authentic assessment approach, the teaching and evaluation of professional competences is discussed. Likewise, two examples of good practice in the Mexican context are offered: a model of electronic portfolio for teacher training and an objective structured clinical examination (OSCE) system in dentistry. In both cases, the understanding and appropriation of the approach in the educational communities was achieved and changes in the curricular management processes that favored its concretion were promoted. This paper concludes with a series of assumptions and conditions associated with the appropriate establishment of systems for authentic assessment of competences at higher level education.